2015
DOI: 10.1515/reveh-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and health in the Eastern Mediterranean countries: a systematic review

Abstract: AbstractTo summarize the existing knowledge of the impact of climate change on health from previous research in the Eastern Mediterranean region (EMR) and identify knowledge and research gaps.Different databases were searched for relevant studies published in the region between 2000 and 2014. The review was limited to studies reporting the impacts of climate change on health or studying associations between meteorological parameters and well-defined human healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The current study showed that the EMRO region had the least contribution despite that the region is expected to suffer from serious climate variations [117]. A systematic review on climate change and health in the EMRO region identified many knowledge and research gaps with research scarcity in this field [118]. The authors of the systematic review concluded that the impact of climate change on health is not recognized as a priority area by health researchers, health professionals and policymakers in the EMRO region.…”
Section: Key Players In Health-and Infection-related Researchmentioning
confidence: 74%
“…The current study showed that the EMRO region had the least contribution despite that the region is expected to suffer from serious climate variations [117]. A systematic review on climate change and health in the EMRO region identified many knowledge and research gaps with research scarcity in this field [118]. The authors of the systematic review concluded that the impact of climate change on health is not recognized as a priority area by health researchers, health professionals and policymakers in the EMRO region.…”
Section: Key Players In Health-and Infection-related Researchmentioning
confidence: 74%
“…Reviews suggest an association of most meteorological factors such as temperature increase, aridity, heat and heat waves with mental health outcomes, including hospital admissions for mental health reasons, 55 suicide, 100 and exacerbation of pre-existing mental health conditions, difficulty sleeping and fatigue. 35 No association was found between sunlight duration and suicide incidence.…”
Section: Meteorological 11mentioning
confidence: 99%
“…CCHF is an occupational disease for livestock workers, butchers, slaughterhouse workers, health care workers, animal husbandry workers and veterinarians who belong to a group of people at high risk of the disease in the endemic areas of CCHF [ 8 ]. The incidence rate increases by many folds during Eid ul Adha, a religious festival during which millions of animals are slaughtered [ 6 , 9 ]. As CCHF is a viral contagious endemic disease, cases of spread of this disease in healthcare professionals have also observed.…”
Section: Introductionmentioning
confidence: 99%